Geometric structure-guided photo-driven ion current through asymmetric graphene oxide membranes. Issue 35 (2nd September 2019) - Feng, Yaping; Dai, Haoyu; Chen, Jianjun; Kong, Xian; Yang, Jinlei; Jiang, Lei
Abstract : A photo-driven ion transport mode is developed that the limitation of the need local illumination. Abstract : It has been demonstrated previously that ion transport can be generated in a graphene oxide membrane (GOM) when light is illuminated on an off-centre position on it, which triggers a transmembrane potential. We show in this work that rational design of the GOM geometry obviates the necessity of partial illumination. Upon full-area light illumination, a net cationic flow through a geometry-asymmetric GOM is generated from the thin side toward the thick side. The origin of the photo-responsiveness of the asymmetric GOM is the synergistic effect of light decay with depth in the GOM and the disparate diffusion rates of charge carriers in the GOM, i.e., electrons and holes. The geometry modulation of the GOM provides a facile and straightforward way to photo-induce ion transport.